(3eHGOF GdEOGQIs - (3cQje efUhQ(B, (3ZGRjs ((3GdEScfOQjI(B:s (3ecJHI GdhaGA GdbGfhfjI(B,s, 2015)
(3jVe ebOeI aj GdEOGQI, GdHjFI,KbGaI GdefXeI hGdJfhY, GdEWGQ GdacQj ddEOGQI, GdJNWjW, GdJfXje GdEOGQj, GdJhLjg, GdQbGHI GdEOGQjI GdbjGOI GdEOGQjI , GdEJUGdGJ GdEOGQjI ,EJNGO GdbQGQGJ GdEOGQjI, EOGQI GdehGQO GdHTQjI , CNdGbjGJ GdEOGQI h GdeSDhdjI GdELJeGYjI ddefXeGJ , GdaQb Hjf GdEOGQI GdYGeI h EOGQI GdCYeGd, eONd GdEOGQI HGdCgOGa , GdEJLGgGJ GdeYGUQI aj GdEOGQIs
Keywords: (3EOGQI GdCYeGds; (3GdEOGQIs; (3GdEOGQI GdYGeIs; (3GdacQ GdEOGQjs